2013
DOI: 10.1016/j.virol.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Porcine reproductive and respiratory syndrome virus activates inflammasomes of porcine alveolar macrophages via its small envelope protein E

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) infection results in extensive tissue inflammation and damage, which are believed to be responsible for increased susceptibility to secondary infection and even for death. However, its pathogenic mechanisms are not fully understood. To explore the mechanism underlying the PRRSV-induced tissue inflammation and damage, we investigated whether PRRSV activates porcine alveolar macrophage (PAM) inflammasomes which mediate por-IL-1β maturation/release and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 32 publications
0
38
1
Order By: Relevance
“…We speculated that there may be other mechanisms involved in NLRP3-independent inflammasome activation during HP-PRRSV infection. Recently, PRRSV structural protein E was found to activate inflammasome and induce IL-1B secretion (49). However, the underlying mechanism was not characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that there may be other mechanisms involved in NLRP3-independent inflammasome activation during HP-PRRSV infection. Recently, PRRSV structural protein E was found to activate inflammasome and induce IL-1B secretion (49). However, the underlying mechanism was not characterized.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1b level was closely correlated with persistent infection and pathogenesis of PRRSV (48). Recently, it has been reported that PRRSV structural protein E was involved in IL-1b secretion (49), and HP-PRRSV infection can induce IL-1b secretion, which depends on the TLR4/MyD88 pathway and NLRP3 inflammasome activation (50).…”
mentioning
confidence: 99%
“…More recently, several members of the picornaviridae family were shown to similarly activate NLRP3 through their 2B protein ion channel including encephalomyocarditis virus, poliovirus, enterovirus 71, and human rhinovirus [41,42]. The SH protein of human respiratory syncytial virus (RSV) also mediates NLRP3 inflammasome activation, as does the E protein of porcine reproductive and respiratory syndrome virus (PRRSV) [43,44]. Clearly, ion flux is a key feature for NLRP3 sensing of viral infection.…”
Section: Nlrp3 Inflammasomementioning
confidence: 99%
“…GFP-PRRSV generation was performed as described previously [3, 10, 35]. The 5′-capped GFP-PRRSV mRNA (Figure 2(a)) was first transcripted by T7 DNA polymerase in vitro with the transcription kit using Acl I-linearized FL12-GFP plasmid as a template (there is a T7 promoter upstream PRRSV genome in FL12 plasmid).…”
Section: Resultsmentioning
confidence: 99%